The Dynamics of the Implementation of Islamic Relligious Education Policy in School: A Literature Review - Umi Sarah Nafi’ah Darojat; Novita Ayu Utari (Edumaspul: Jurnal Pendidikan, 2024)
The Islamic Religious Education policies is basically clearly stated in Pancasila and the 1945 Constitution, which the government then reviews and implements in all its development processes. This research aims to find out and analyze the implementation of Islamic Religious Education policies in schools which includes a brief history of Islamic Religious Education policies in schools, scope of data, implementation efforts, and problems and solutions. This research uses library research methods taken from various primary and secondary sources. The results of this research are: 1) Islamic Religious Education policies in schools are part of the national education system whose implementation is regulated by the National Education System Law Number 20 of 2003, Government Regulation Number 55 of 2007, and Law of 1950 Chapter XII Article 20 Paragraph 1. 2) Current implementation of Islamic Religious Education in schools is a subject that is required to be held in schools, both state and private schools and is applied at all levels. 3) The main problem with Islamic Religious Education policies in schools is that the time allocation is very low, requiring teachers to be able to convey the material completely and comprehensively through several activities outside of class